Synthesis, characterization, antituberculosis activity and computational studies on novel Schiff bases of 1,3,4-thiadiazole derivatives - KARAKUŞ, SEVGİ (MARMARA UNIV, 2020)
A series of novel Schiff bases were designed and synthesized by the condensation of 1,3,4-thiadiazoles that contain aromatic primary amine and variously substituted benzaldehydes. The synthesized compounds were screened for their antituberculosis activity against Mycobacterium tuberculosis H(37)Rv using BACI EC 460 radiometric system. Among the tested compounds, 2-(4-nitrophenyl)amino-5-[4-(3-(4-phenoxy))benzylideneaminophenyl]-1,3,4-thiadiazole (3n) showed the highest inhibitory activity (80%). The activities of the newly synthesized Schiff bases were higher in comparison to those of intermediate products 2-(4-aminophenyl)-5-aryl/alkylamino-1,3,4-thiadiazoles (2a-l). The computational studies were also performed to estimate drug-like profile of the compounds by using QikProp analysis.
Keywords: Schiff bases; 1,3,4-thiadiazoles; antituberculosis activity; Mycobacterium tuberculosis H(37)Rv; ADME; TUBERCULOSIS; HYDRAZIDE; COMPLEXES; DFT